Slow Wave Applications of Electromagnetically Induced Transparency in Microstrip Resonator - Muhammad Amin (Nature Portfolio, 2018)
Abstract We report a novel guided-wave resonator that supports multiple bands of electromagnetically induced transparency (EIT). The platform for the spatial and spectral interference is obtained by a microstrip transmission line loaded with proximity-coupled open-circuited stubs. We show experimentally that with two microstrip open stubs, a complete destructive interference takes place leading to a single EIT band with near-unity transmission efficiency. More interestingly, the addition of a third stub results in a supplementary EIT band with a Q-factor of 147 and an effective group refractive index of 530. With the open-stub configuration, the EIT phase response can be dynamically controlled by varying the capacitance between the adjacent stubs without breaking the transmission path of the underlying electromagnetic waves. Therefore, the proposed structure is well suited for buffering and tunable phase modulation applications. Since the proposed structures are compact and fully planar, we anticipate seamless integration with low-profile high frequency electronics.